KOMPARASI PERANAN SEKTOR PERTANIAN TERHADAP PENGANGGURAN ANTAR DEKADE SETELAH PERIODE REFORMASI DI INDONESIA - Rizqy, Yusriani; Bahari, Doddy Ismunandar; Nursalam (Department of Social Economic Agriculture, Faculty of Agriculture, University of Papua, Manokwari, West Papua, Indonesia, 2023)
Unemployment is still a big problem in Indonesia is the problem of unemployment. High levels of unemployment can have a direct impact on various aspects of life, especially economic aspects. Therefore, the aim of this research was to determine the relationship the role of the agricultural sector and the unemployment rate between two decades after reformation order in Indonesia. The data source used was secondary data which obtained from the Southeast Sulawesi Central Statistics Agency of Indonesia. The research method used was a quantitative descriptive approach which is scatter plot pattern analysis techniques and bivariate correlation analysis with time series data for 1998-2020. The research results show the pattern of unemployment growth and agricultural economic growth from the scatter plot results, namely Y = -10,348x + 38,356, which means the trendline is negative with an R2 value of 0.5046 or 50.46%, which means the agricultural sector plays an important role in labor absorption. Furthermore, bivariate correlation results show a significance value between unemployment and Gross Domestic Product (GDP) in the agricultural sector of 0.0001 < 0.05 and a correlation index value of 0.710 with a negative sign. This value is smaller than the value of 0.5, which means that the agricultural sector plays a role in reducing unemployment in Indonesia. The results of a comparison of the role of the agricultural sector in unemployment between decades show that the agricultural sector is increasingly responsive to absorb labor and it potentially to reduce the unemployment rate in Indonesia.